Numerical research of thermal and stress-strain state of high-pressure rotor of turbine type t-100/120-130 of 1st power unit «Kharkiv CHPP-5» - Chernousenko, Olga Yuriivna; Peshko, Vitaliy Anatoliyovich (Вісник Національного технічного університету «ХПІ». Серія: Енергетичнi та теплотехнiчнi процеси й устаткування, 2017)
Preferred direction of development of district heating in large cities, according to the European Union directive, is the development of cogeneration to 10% of the total production of electric energy. For steam turbines type T‑100/120-130 developed a mathematical model of thermal and stress-strain state on the basis of 3D-dimensional analogues for the high pressure rotor, taking into account existing damage to the project design and repair or any changes of elements in the operation. The results of research include calculation of the thermal and stress-strain state of the high pressure rotor of steam turbine type T-100/120-130 of first power unit OJSC "Kharkiv CHPP-5". In the process of analyzing the results it was determined maximum loaded area of the rotor at each start-up operating modes: starting from cold, still hot from previous and hot conditions. Values of the maximum amplitude of the stress intensity were established for the most loaded sections of the rotor, they are allow to estimate the low-cycle fatigue and residual service life-time of the main metal of the turbine.